Designed and Development of Bluetooth Based Smart Home Automation System for Disabled People - Saadon, Eddy Irwan Shah; Tukiran, Zarina; Ismail, Nurulhuda; Ismail, Muhammad Faizal (Multidisciplinary Applied Research and Innovation, 2021)
This project is designed to control electrical appliances and monitor ambient temperature from a smartphone. This project actually can assist and provide support to kids, elderly and disabled at home. The design is using an Arduino Uno board and the home appliances are physically connected to input/output ports via relays. The main control system connected via wireless Bluetooth technology to provide remote access from a tablet or smartphone. Cytron  BlueBee used  to establish  communication between an Android  phone  and  the Arduino Uno board wirelessly.  The system is intended to control electrical appliances and devices in home with friendly user interface and trouble-free installation. From the analysis, the most efficient Bluetooth connection for a close area is around 15m and 20m for the open area.